Imprisoned intellectuals : America's political prisoners write on life, liberation, and rebellion - James, Joy, 1958- (Transformative politics series., 2003)
These essays, by writer-activists incarcerated because of their political beliefs and acts, offer some controversial and thought-provoking theories of contemporary social change and liberation movements.